2010
DOI: 10.1021/ic100494f
|View full text |Cite
|
Sign up to set email alerts
|

Basic Coordination Chemistry Relevant to DNA Adducts Formed by the Cisplatin Anticancer Drug. NMR Studies on Compounds with Sterically Crowded Chiral Ligands

Abstract: Me(4)DABPtG(2) adducts with the bulky C(2)-symmetric chiral diamine, Me(4)DAB (N,N,N',N'-tetramethyl-2,3-diaminobutane with R,R and S,S configurations at the chelate ring C atom, G = guanine derivative), exhibit slow conformer interchange and are amenable to characterization by NMR methods. The investigation of the cis-PtA(2)G(2) adducts formed by clinically widely used anticancer drugs [A(2) = diaminocyclohexane, (NH(3))(2)] is impeded by the rapid conformer interchange permitted by the low A(2) bulk near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 60 publications
(358 reference statements)
8
38
0
Order By: Relevance
“…It is well known that cisplatin can cross the cell membrane by passive diffusion [ 32 , 33 , 34 ], or using selected ion channels [ 35 ]. Once inside the cytosol, aquation processes activate the drug, increasing its reactivity toward DNA (essentially at the purines N7 electron donors, which are considered the main pharmacological targets of cisplatin) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that cisplatin can cross the cell membrane by passive diffusion [ 32 , 33 , 34 ], or using selected ion channels [ 35 ]. Once inside the cytosol, aquation processes activate the drug, increasing its reactivity toward DNA (essentially at the purines N7 electron donors, which are considered the main pharmacological targets of cisplatin) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism underlying CP-induced toxicity remains to be fully elucidated. Previous studies have demonstrated that the anticancer behavior of CP originates from its capacity to attach to the N-7 position of purine bases of cellular DNA causing mono-adducts formation, which are converted into inter-and intra-strand cross links with a reaction at the secondary reactive site of drug together with the second nucleobase (3)(4)(5). Mitochondria have been revealed to be the cellular power plants (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In Pt(II) adducts with DNA, the G* nucleobase orientation is strongly influenced by a combination of the DNA structure and the steric interactions of the nucleobase with the carrier ligand. 29,30 Considerable effort has been expended in studying Pt(L)(G) 2 models and in comparing results to related G*G* intrastrand models with short oligonucleotides. 12,20,29,31−33 Both model types can have as many as two head-to-head (HH) and two head-to-tail (HT) rotamers, depending on the bulk and symmetry of L ( Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%